A song of flight - Marillier, Juliet (Marillier, Juliet. Warrior bards series., 2021)
"A young warrior who wields both the power of her music and the strength of her sword faces a grave threat in this enthralling historical fantasy. Bard and fighter Liobhan is always ready for a challenge. So when news arrives at Swan Island that the prince of Dalriada has gone missing after an assault by both masked men and the sinister Crow Folk, she's eager to act. While Liobhan and her fellow Swan Island warriors seek answers to the prince's disappearance, the bard Brocc, Liobhan's brother, finds himself in dire trouble. His attempts to communicate with the Crow Folk have led him down a perilous path. When Liobhan and her comrades are sent to the rescue, it becomes clear the two missions are connected-and a great mystery unfolds. What brought the Crow Folk to Erin? And who seeks to use them in an unscrupulous bid for power? As Liobhan and Brocc investigate, it will take all their strength and will to continue pursuing the truth. With the safety of their loved ones in the balance, the risks they must take may cost them everything"--